Uric acid and glaucoma: a systematic review and meta-analysis - Mohammadi, Mohammad; Yarmohammadi, Adeleh; Salehi-Abargouei, Amin; Ghasemirad, Hamidreza; Shirvani, Mohammad; Ghoshouni, Hamed (Frontiers in Medicine, 2023)
Background Glaucoma, the leading cause of irreversible blindness, is a common disorder that contributes to gradual optic nerve degeneration. The beneficial impacts of uric acid (UA) have been reported in some neurodegenerative conditions such as Parkinson's disease, Alzheimer's disease, and amyotrophic lateral sclerosis. But the results of current studies about the association between serum UA level and glaucoma are conflicting. The present meta-analysis was conducted to provide a better understanding of the association between serum UA level and glaucoma. Methods We searched the databases of PubMed, Scopus, Web of Science, and Google Scholar systematically until November 20, 2022 to identify case-control studies, comparing the serum UA concentrations of the patients with glaucoma and controls. The mean ± standard division difference was used to assess the difference in serum UA concentrations between the glaucoma patients and controls. Results Six studies involving 1,221 glaucoma patients and 1,342 control group were included in the present meta-analysis. This meta-analysis using a random effect model indicated that the mean UA level in glaucoma patients was 0.13 (I2 = 91.92%, 95% CI = −0.42 to 0.68) higher than the controls; however, it was not statistically significant. Conclusions Our findings provide evidence that glaucoma patients have a higher serum UA level compared to the controls, but this difference is not statistically significant. Prospective studies are needed to determine the possible association between increased UA and glaucoma pathogenesis. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022364055, identifier: CRD42022364055.